Communication Latency Evaluation on a Software-Defined Network-on-Chip - Silva, Raul Silveira; Cruz , Patricia; Kreutz, Márcio; Pereira, Monica (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
In conventional NoCs, it is common to use deterministic routing algorithms, which defines a unique route for communication between two processing cores and are implemented in hardware on the routers modules. However, the problem with having only one possible route between source and destination is the lack of alternative paths in case there is congestion or even obstructions along the route. A more recent approach to cope with this problem is the use of another NoCs paradigm which the routing algorithms are implemented in software, the Software-Defined Networks-on-Chip (SDNoCs). In this approach, the routing algorithm is executed by a core manager which creates and destroys virtual circuits to provide the communication between other cores, allowing the use of adaptive routing algorithms, which avoids deadlocks and provides more flexibility in creating the routes. The present work describes the proposal and implementation of a SDNoC, also presenting an investigation on its behavior when the traffics message exchange increases. Furthermore, the communication latency was evaluated over a deterministic and an adaptive routing algorithms. Finally, the experimental results the adaptive algorithm achieved better communication performance for a set of task graphs, reaching up to 3.6x of speedup comparing to the deterministic approach.